Surgical correction of presbyopia. Issue 6 (June 2016) - Davidson, Richard S.; Dhaliwal, Deepinder; Hamilton, Rex D.; Jackson, Mitchell; Patterson, Larry; Stonecipher, Karl; Yoo, Sonia H.; Braga‐Mele, Rosa; Donaldson, Kendall
Abstract : N/A: Presbyopia is the most common refractive disorder for people older than 40 years. It is characterized by a gradual and progressive decrease in accommodative amplitude. Many surgical procedures for the correction of presbyopia exist, with additional procedures on the horizon. This review describes the prevalent theories of presbyopia and discusses the available surgical options for correction. Financial Disclosure : Proprietary or commercial disclosures are listed after the references.